The impact of computer use on the achievement of students of the College of Administration and Economics, University of Baghdad, in the Arabic language subject (Journal of the College of Basic Education, 2023)
The phenomenon of linguistic weakness has become a common occurrence among students at various stages of education, and it is one of the important problems in language education. The student who graduated from school, or even one who graduated from university, does not read as he should read, nor write as he should write, as he makes many mistakes in spelling when he dictates. He has many grammatical errors when he speaks or writes, and his thoughts do not take place in a sequential manner and he uses words anxiously. The problem of the difficulty of studying the Arabic language still exists, as it is still difficult and the complaints about it continue, and the weakness of the students in it is almost comprehensive and general, as it is not determined by one stage of study without another, or by one academic class without another, as the learners complain about the dryness of the Arabic language curricula offered In all stages of general education, students notice a large number of grammatical errors that they make, and their inability to properly set the end of words in pronunciation and writing (Abdul-Hadi et al., 2005, p. 312). technology in which the whole world lives, and its direction towards education through modern technologies, the researcher sought to employ the computer subject in teaching the Arabic language as the most developed machine in the world because of its great ability to display and store details, which prompted the researcher to develop the process of teaching the subject The Arabic language using this technique, hoping that it will bear the desired fruits and raise students’ achievement in this subject.